Humoral immunity is sufficient to protect mice against Rift Valley fever encephalitis following percutaneous exposure - Karina Mueller Brown; Dominique J. Barbeau; Lingqing Xu; Brian H. Bird; Anita K. McElroy (npj Vaccines)
Abstract In humans, Rift Valley fever virus (RVFV) infection typically presents as a self-limiting febrile illness but can cause severe complications. Neurological disease manifestations are particularly concerning as they are associated with increased mortality and long-term morbidity. This study demonstrated that vaccination with live attenuated RVFV was effective in preventing central nervous system (CNS) disease in the CC057/Unc mouse model of late-onset RVF encephalitis. Vaccine candidates (ΔNSs and ΔNSsΔNSm) were safe and immunogenic and elicited both RVFV-specific humoral and cellular immunity. Vaccinated mice survived percutaneous wild-type (WT) RVFV challenge and were protected from CNS disease. Naïve mice that received passive transfer of serum from vaccinated animals 2 days post-WT challenge were protected against late-onset encephalitis. These data demonstrate that humoral immunity is sufficient to protect against RVF encephalitis in CC057/Unc mice and suggest the potential of these vaccine candidates to prevent CNS disease in humans.